Five-component, one-pot synthesis of an electroactive rotaxane comprising a bisferrocene macrocycle - Lagesse, Natalie; Pisciottani, Luca; Douarre, Maxime; Godard, Pascale; Kauffmann, Brice; Martí-Centelles, Vicente; McClenaghan, Nathan D. (Beilstein Journal of Organic Chemistry, 2020)
The templated clipping of a ferrocene-grafted isophthalic acid derivative to encircle a hydrogen-bonding axle through the reaction with 1,4-bis(aminomethyl)benzene is described. The constituent electroactive macrocycle of the resultant [2]rotaxane is a homologue of the versatile benchmark tetraamide variant developed by Leigh and co-workers. The relative templating effect of different hydrogen-bonding motifs in rotaxane and pseudorotaxane generation is compared, with yields varying from 0 to 41%. The electrochemical properties and single crystal X-ray structure of a doubly ferrocene-decorated [2]rotaxane are further reported.
Keywords: ferrocene; macrocycle; rotaxane; single crystal X-ray structure; template